Kinerja Pegawai Perpustakaan Sekolah dalam Peningkatan Pelayanan - Dwi Hermawan, Guntur; Dwi Jayanti, Oni; Rofik, Rofik (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2022)
Optimization of library services in schools can be caused by various factors, one factor that is quite important is the performance of library staff. Based on the problems above, the writer really needs to try to research to solve these problems. The aims of the research are: (1) to find out the performance of school librarian employees; and (2) improving the quality of school library services through the performance of library staff. The research method uses a qualitative approach and a descriptive research type. The types of data used in this research are: (1) primary data relating to the research focus and (2) secondary data: documents; reports; and archives related to research. The method of collecting research data that the authors used in this study were as follows: (1) observation techniques; (2) interviews, and (3) distribution of questionnaires and questionnaires. The research instruments used were: (1) interview guidelines; (2) field notes or stationery; (3) distributing questionnaires to predetermined respondents. The findings of this study are: (1) the responsiveness of services in the school library is still low as indicated by the persistence of complaints from service users against school library service providers; (2) the reliability of school library service officers is still not relevant, this can be seen from the incomplete collection of school libraries in meeting the needs of service users; (3) school library service ethics are still low and not in accordance with the National Library service standards. Staff lack respect and seem indifferent to users, this makes users less interested in coming to the school library; (4) school library service facilities have not shown good service performance, this can be seen by the number of users who are still not comfortable with the arrangement of library facilities and the cleanliness has not been maintained.